Coordination chemistry and photoswitching of dinuclear macrocyclic cadmium-, nickel-, and zinc complexes containing azobenzene carboxylato co-ligands - Klose, Jennifer; Severin, Tobias; Hahn, Peter; Jeremies, Alexander; Bergmann, Jens; Fuhrmann, Daniel; Griebel, Jan; Abel, Bernd; Kersting, Berthold (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of mixed-ligand complexes of the type [M2L(μ-L')]+, where L represents a 24-membered macrocyclic hexaaza-dithiophenolate ligand, L' is an azobenzene carboxylate co-ligand, and M = Cd(II), Ni(II) or Zn(II), is reported. A series of new complexes were synthesized, namely [M2L(μ-L')]+ (L' = azo-H, M = Cd (1), Ni (2); L' = azo-OH, M = Zn (3), Ni (4); L' = azo-NMe2, M = Zn (5), Cd (6), Ni (7); L' = azo-CO2Me, M = Cd (8), Ni (9)), and characterized by elemental analysis, electrospray ionization mass spectrometry (ESIMS), IR, UV–vis and NMR spectroscopy (for diamagnetic Zn and Cd complexes) and X-ray single crystal structure analysis. The crystal structures of 3' and 5–8 display an isostructural series of compounds with bridging azobenzene carboxylates in the trans form. The paramagnetic Ni complexes 2, 4 and 7 reveal a weak ferromagnetic exchange interaction with magnetic exchange coupling constant values between 21 and 23 cm−1 (H = −2JS1S2). Irradiation of 1 with λ = 365 nm reveals a photoisomerization of the co-ligand from the trans to the cis form.
Keywords: azobenzene carboxylates; cadmium; complexes; macrocyclic ligands; nickel; zinc

(untitled) - Lehmann, U.; Klingele, J.; Lozan, V.; Steinfeld, G.; Klingele, M. H.; Käss, S.; Rodenstein, A.; Kersting, B. (Inorg. Chem., 2010)

(untitled) - Steinfeld, G.; Lozan, V.; Kersting, B. (Angew. Chem., 2003)
Angew. Chem., Int. Ed. 2003, 42, 2261–2263. doi:10.1002/anie.200351131

(untitled) - Käss, S.; Gregor, T.; Kersting, B. (Angew. Chem., 2006)
Angew. Chem., Int. Ed. 2006, 45 , 101–104. doi:10.1002/anie.200500683

(untitled) - Käss, S.; Kersting, B. (Eur. J. Inorg. Chem., 2012)

(untitled) - Lee, K. A.; Lozan, V.; Langford, S. J.; Kersting, B. (Dalton Trans., 2009)

(untitled) - Lozan, V.; Buchholz, A.; Plass, W.; Kersting, B. (Chem. – Eur. J., 2007)

Infrared and Raman Spectra of Inorganic and Coordination Compounds - Nakamoto, K. (John Wiley & Sons, Inc., 1997)

(untitled) - Deacon, G. B.; Philipp, R. J. (Coord. Chem. Rev., 1980)

(untitled) - Martini, D.; Pellei, M.; Pettinari, C.; Skelton, B. W.; White, A. H. (Inorg. Chim. Acta, 2002)

(untitled) - Lozan, V.; Kersting, B. (Eur. J. Inorg. Chem., 2005)

(untitled) - Lach, J.; Hahn, T.; Kersting, B.; Kortus, J. (Eur. J. Inorg. Chem., 2012)

(untitled) - Gressenbuch, M.; Kersting, B. (Eur. J. Inorg. Chem., 2007)

(untitled) - Börner, M.; Blömer, L.; Kischel, M.; Richter, P.; Salvan, G.; Zahn, D. R. T.; Siles, P. F.; Fuentes, M. E. N.; Bufon, C. C. B.; Grimm, D.; Schmidt, O. G.; Breite, D.; et al. (Beilstein J. Nanotechnol., 2017)

(untitled) - Lozan, V.; Loose, C.; Kortus, J.; Kersting, B. (Coord. Chem. Rev., 2009)

(untitled) - Journaux, Y.; Glaser, T.; Steinfeld, G.; Lozan, V.; Kersting, B. (Dalton Trans., 2006)

(untitled) - Lach, J.; Jeremies, A.; Breite, D.; Abel, B.; Mahns, B.; Knupfer, M.; Matulis, V.; Ivashkevich, O. A.; Kersting, B. (Inorg. Chem., 2014)

(untitled) - Ginsberg, A. P.; Martin, R. L.; Brookes, R. W.; Sherwood, R. C. (Inorg. Chem., 1972)

Molecular Magnetism - Kahn, O. (VCH Verlagsgesellschaft, 1993)

Magnetochemistry-Advances in Theory and Experimentation - O’Connor, C. J. (John Wiley & Sons, 2007)

Moderne Anorganische Chemie - Janiak, C.; Klapötke, T.; Meyer, H.-J.; Alsfasser, R. (de Gruyter, 2007)

(untitled) - Azuah, R. T.; Kneller, L. R.; Qiu, Y.; Tregenna-Piggott, P. L. W.; Brown, C. M.; Copley, J. R. D.; Dimeo, R. M. (J. Res. Natl. Inst. Stand. Technol., 2009)

(untitled) - Herchel, R.; Boča, R.; Krzystek, J.; Ozarowski, A.; Durán, M.; van Slageren, J. (J. Am. Chem. Soc., 2007)

(untitled) - Nanda, K. K.; Addison, A. W.; Paterson, N.; Sinn, E.; Thompson, L. K.; Sakaguchi, U. (Inorg. Chem., 1998)

(untitled) - Casimiro, L.; Groppi, J.; Baroncini, M.; La Rosa, M.; Credi, A.; Silvi, S. (Photochem. Photobiol. Sci., 2018)

(untitled) - Klajn, R. (Pure Appl. Chem., 2010)

Spektroskopische Methoden in der organischen Chemie - Hesse, M.; Meier, H.; Zeeh, B. (Georg Thieme Verlag, 2005)

(untitled) - Herzog, S.; Dehnert, J. (Z. Chem., 1964)

(untitled) - Kersting, B.; Steinfeld, G. (Chem. Commun., 2001)

(untitled) - Gressenbuch, M.; Lozan, V.; Steinfeld, G.; Kersting, B. (Eur. J. Inorg. Chem., 2005)

(untitled) - Fujita, K.; Fujiwara, S.; Yamada, T.; Tsuchido, Y.; Hashimoto, T.; Hayashita, T. (J. Org. Chem., 2017)

(untitled) - Pospíšil, J.; Potáček, M. (Tetrahedron, 2007)

(untitled) - Chen, S.; Ling, A.; Zhang, H.-L. (J. Polym. Sci., Part A: Polym. Chem., 2013)

(untitled) - Sahu, S.; Sinha, N.; Bhutia, S. K.; Majhi, M.; Mohapatra, S. (J. Mater. Chem. B, 2014)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 1990)

SHELXL-97, Computer program for crystal structure refinement (University of Göttingen, 1997)

PLATON − A Multipurpose Crystallographic Tool (Utrecht University, 2000)

(untitled) - Farrugia, L. J. (J. Appl. Crystallogr., 1997)

(untitled) - Spek, A. L. (Acta Crystallogr., Sect. D: Biol. Crystallogr., 2009)